Pengaruh Kualitas Produk Tabungan Idul Fitri dan Bagi Hasil terhadap Minat Menabung Anggota Pada BMT UGT Nusantara Capem Purwoharjo - Khikmah, Lutfiyatul; Azhar, Indana Almas (Universitas Batanghari Jambi, 2025)
This study was conducted to determine the effect of the Quality of Idul Fitri Savings products and profit sharing on the interest in saving members at BMT UGT Nusantara Capem Purwoharjo. The method used in this study is quantitative descriptive. The sampling technique was purposive sampling, namely on active members saving for the last five years as many as 89 members. The results of the study showed that simultaneously and partially there was a positive and significant influence between the variables of product quality and profit sharing on the interest in saving members of Idul Fitri savings at BMT UGT Nusantara Capem Purwoharjo. The Determination Coefficient value of 0.298 indicates that 29.8% of interest in saving is influenced by the variable of product quality and the variable of profit sharing.